Collembola Community Structure as a Tool to Assess Land Use Effects on Soil Quality - Oliveira Filho, Luís Carlos Iuñes de (2016)
Collembolan species are differently affected by soil tillage (conventional, minimum tillage, and no-tillage) and are known to modify plant growth. This study relies on the relationships between Collembola community structures and land use systems as a proxy for characterizing changes in soil quality. Thus, Collembola community structure (eco-morphological groups – edaphic, hemiedaphic and epigeic, and morphotypes) were examined in a no-tillage system and crop-livestock integration system to evaluate the discriminative power of the Collembola community structure and to determine which soil properties drives structural diversity. Thirty-eight morphotypes of Collembola were recorded in this study, 11 belonging to the edaphic eco-morphological group, 14 hemiedaphic, and 13 epigeic. The hemiedaphic and epigeic groups, in the no-tillage system, were more influenced by changes in soil properties (total organic carbon, particulate organic carbon, total N, Ca, Mg, moisture, bulk density) and mycelium length than the groups in the crop-livestock integration system (mycorrhizal inoculum potential, and soil properties as dehydrogenase, particulate organic carbon, Mg, sand). Collembola eco-morphological groups were better predictors for ecosystem functioning than Collembola density and can be used to distinguish differences between soil uses, reducing laboratory analysis time.